CAvant® WO-60 as an Effective Immunological Adjuvant for Avian Influenza and Newcastle Disease Vaccine - Lee, Eun-Seo; Shim, Young-Jung; Chathuranga, W. A. Gayan; Ahn, Young-Hoon; Yoon, In-Joong; Yoo, Sung-Sik; Lee, Jong-Soo (Frontiers in Veterinary Science, 2021)
Despite the immunogenicity of vaccines currently used in poultry, several pathogens, including avian influenza virus (AIV) and Newcastle disease virus (NDV), cause enormous economic losses to the global poultry industry. The efficacy of vaccines can be improved by the introduction of effective adjuvants. This study evaluated a novel water-in-oil emulsion adjuvant, CAvant® WO-60, which effectively enhanced both the immunogenicity of conserved influenza antigen sM2HA2 and inactivated whole H9N2 antigen (iH9N2). CAvant® WO-60 induced both humoral and cell-mediated immunity in mice and provided 100% protection from challenge with 10 LD50 of A/Aquatic bird/Korea/W81/2005 (H5N2) and A/Chicken/Korea/116/2004 (H9N2) AIV. Importantly, immunization of chickens with iH9N2 plus inactivated NDV LaSota (iNDV) bivalent inactivated vaccine emulsified in CAvant® WO-60 induced seroprotective levels of antigen-specific antibody responses. Taken together, these results suggested that CAvant® WO-60 is a promising adjuvant for poultry vaccines.